2012
DOI: 10.1055/s-0032-1304951
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologisch-klinische Charakteristika von Patienten mit zystischer Echinokokkose

Abstract: The diagnosis of CE is delayed by the paucity of characteristic symptoms and the inconsistency of serologic results. Assessment of cyst morphology and localisation are particularly important for diagnosis, staging and follow-up. CE requires an interdisciplinary management which should be coordinated by specialized infectious diseases centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The reactivity of rural inhabitants to Echinococcus antigens was significantly greater compared to urban dwellers, which confirms the views of Romig et al(2003) Bobić et al (2012) and Orhun et al (2012). The ELISA results obtained in the current study showed a decrease in seropositive reactions with age, and did not confirm the view of the greatest frequency of echinococcosis in older people (Torgerson, 2013).…”
Section: Percent Of Positivesupporting
confidence: 58%
“…The reactivity of rural inhabitants to Echinococcus antigens was significantly greater compared to urban dwellers, which confirms the views of Romig et al(2003) Bobić et al (2012) and Orhun et al (2012). The ELISA results obtained in the current study showed a decrease in seropositive reactions with age, and did not confirm the view of the greatest frequency of echinococcosis in older people (Torgerson, 2013).…”
Section: Percent Of Positivesupporting
confidence: 58%
“…This is not uncommon for countries characterized by high immigration rates. For example, in a study conducted in Germany, only nine out of 65 cystic echinococcosis cases were of German origin [ 63 ]. In another German study, AE was diagnosed in a refugee from an endemic area (e.g.…”
Section: Human Infections With Echinococcus Multilocularis mentioning
confidence: 99%
“…Furthermore, the present study reveals more detailed epidemiological and clinical data which are helpful for further steps in the future control and management of CE in Albania (Casulli et al 2022). From the experience of other studies, it results that hospital records largely underreport CE cases as compared to populationbased surveys (Budke et al 2006;Casulli et al 2022;Orhun et al 2012;Richter et al 2019). Anyhow, from our data results that there is a decrease of cases over the last 10 years which is likely to be due to the high emigration rate from rural areas and urbanization of the Albanian population.…”
Section: Discussionmentioning
confidence: 62%
“…Rural areas with most intensive sheep raising are likely to be the places of most intensive transmission such as the rural areas of Gjirokastër, Kukës and Dibër counties. Surgery rate in the three case series was between 84% and 91%, a very high rate in comparison with other endemic countries (Orhun et al 2012;Velasco-Tirado et al 2018). Although there is no unique gold standard therapy for complex clinical cases such as CE, the high surgery rate suggests that other therapy options are rarely considered.…”
Section: Discussionmentioning
confidence: 81%